Mathematics and computation in music : 5th International Conference, MCM 2015, London, UK, June 22-25, 2015, Proceedings /: 5th International Conference, MCM 2015, London, UK, June 22-25, 2015, Proceedings. (2015) - Unknown
No abstract available